Sodium vanadium titanium phosphate electrode for symmetric sodium-ion batteries with high power and long lifespan - Dongxue Wang; Xiaofei Bie; Qiang Fu; Ditty Dixon; Natalia Bramnik; Yong-Sheng Hu; Francois Fauth; Yingjin Wei; Helmut Ehrenberg; Gang Chen; Fei Du (Nature Communications, 2017)
Discovering suitable electrodes is a challenge for the development of sodium-ion batteries. Here the authors demonstrate a high-performance symmetric battery based on Na2VTi(PO4)3, highlighting its potential application in a smart grid.